Natural convection in an inclined porous triangular enclosure with various thermal boundary conditions - Sivasankaran, Sivanandam; Cheong, Huey Tyng; Bhuvaneswari, Marimuthu (VINCA Institute of Nuclear Sciences, 2018)
The aim of the study is to analyze the effect of two different thermal boundary conditions on natural convection in a porous triangular enclosure. Sinusoidal and linearly varying temperature profiles on the left wall are considered. The top wall of the enclosure is kept to be adiabatic. The Darcy model is adopted in this study and the governing equations are solved using the finite difference method for various values of inclination angle and Darcy-Rayleigh number. The results are presented in the form of streamlines, isotherms and Nusselt numbers. The heat transfer rates are calculated and compared between two thermal boundary conditions. The heat transfer is more enhanced in the case of sinusoidal wall temperature than linearly varying wall temperature.